The Role of Indigenous Community Paralegals in Providing Legal Aid Case Study of Sorong Regency - Hulihulis, Mustafa; Naim, Sokhib; Hasriyanti, Hasriyanti; Mustamar Keliobas; Kariadi, Kariadi (Journal of Law Justice (JLJ), 2024)
Indonesia as a state of law is faced with the challenge of providing legal protection to indigenous peoples, who are often marginalized and vulnerable to rights violations. Using an empirical juridical research method, this study explores the role of paralegals in providing legal aid and identifies the obstacles faced. Paralegals, despite not having a formal legal education background, play a key role in providing access to justice to communities in need. They act as a liaison between advocates and the poor, especially in rural or remote areas that are difficult to reach by advocates. The legal aid program, as mandated by Law No. 16/2011, gives legitimacy to the role of paralegals in providing access to justice. However, the implementation of the paralegal role is not without obstacles. These include limited access to legal training, lack of understanding of the role of paralegals in the community, and challenges in gaining access to justice for the communities they serve. Nevertheless, the existence of paralegals is crucial in providing access to justice for underprivileged or marginalized communities. This study concludes that strengthening the role of paralegals in providing legal aid is a concrete step in supporting access to justice for the poor or marginalized. Efforts are needed to increase understanding and knowledge of the role of paralegals and strengthen cooperation between paralegals, advocates, and other legal aid institutions. Thus, paralegals can be more effective in carrying out their duties in providing access to justice for all levels of society, especially those in need.